Fixing to die - James, Miranda (James, Miranda. Southern ladies mysteries., 2017)
It's autumn down south, and An'gel and Dickce Ducote are in Natchez, Mississippi, at the request of Mary Turner Catlin, the granddaughter of an old friend. Mary and her husband, Henry Howard, live in Cliffwood, one of the beautiful antebellum homes for which Natchez is famous. Odd things have been happening in the house for years, and the French Room in particular has become the focal point for spooky sensations. The Ducotes suspect the ghostly goings-on are caused by the living, but when a relative of the Catlins is found dead in the room, An'gel and Dickce must sift through a haunted family history to catch a killer.